5 Years Retrospective Study of Child Sexual Abuse at Dr. M. Djamil Hospital Padang Indonesia - Taufik Hidayat; Rika Susanti; Citra Manela (Universitas Andalas, 2020)
Introduction. The purpose of this study was to analyze the profile of child sexual abuse cases. Methods. The research design was a cross-sectional analytic method. Data were obtained from medical records of child sexual abuse at Dr. M. Djamil Hospital Padang from 2012 to 2016. The sample was 114 medical records of child sexual abuse. Results. The highest incident was in the year of 2015 (28.9%). The highest age range of the victims was 11-18 years old (66.7%). Most victims were junior high school students (27.2%). The highest incident was rape (38.6%). Many of the victims were assaulted by 1 perpetrator (85.1%). An intact hymen was found in 20.2% cases and the highest non-intact hymen was old complete laceration (27.2%), The highest external genitalia examination result was no injuries (69.3%). Most of the victims had previous sexual experience (31.6%). The most commonplace of sexual abuse was the perpetrator's house (21.9%). The boyfriend was the highest rank of the sexual perpetrator (27.1%). There was a significant relationship between child sexual abuse category and status of the hymen (p=0.00). Conclusion. Child sexual abuse categorized as molestation, rape and consent sex, while rape was the highest incident of child sexual abuse. There were various hymen lacerations had found in the victims of child sexual abuse.